Pengaruh Digital Banking dan Efisiensi Operasional Terhadap Kinerja Pelayanan Pada PT Bank Sulselbar Cabang Antang - Asmi Anugrah; Rifqi Nur Wahyudi (Journal Axegnal: Tax And Economic Insights Journal, 2025)
Abstrack The aim of this research is to analyze the influence of digital banking developments and operational efficiency on service performance at  Bank Sulselbar Antang Branch. The main issues raised were regarding limited technological infrastructure and low customer digital literacy in the implementation of digital banking. This research uses a mix methods approach with primary data from questionnaires, interviews, and secondary data from related documents. The analysis technique used is multiple linear regression analysis to measure the relationship between variables. The results of this research show that digital banking significantly increases operational efficiency and service performance through reducing manual processes and increasing productivity. However, customers' lack of digital literacy hinders oimizing the benefits of technology. Operational efficiency is proven to contribute to the literature on digital transformation in the banking sector, especially in regional banks, as well as offering strategic recommendations to increase competitiveness through digitalization. The implications include increasing operational efficiency, customer satisfaction, and implementing Islamic sharia values ​​in digital banking services.